Politik Islam antara Dakwah dan Orientasi Kekuasaan - Zainal Fikri (UIN Antasari Banjarmasin, 2014)
This paper discusses the Islamic politics between the orientation of dakwah and power. Although dakwah was originally synonymous with cultural efforts, but the efforts of those who pull dakwah into the circle of jihad and politics have changed the meaning of the dakwah. In political Islam, dakwah is identical with political purposes of Islam itself, namely the establishment of Sharia and Islamic State. However, the other parties politicize Islam to gain power. According to some people, political parties, including the Islamic party, in Indonesia, politicize Islam rather than fight for Islam